FROM CHILDHOOD WOUNDS TO HEALERS: UNDERSTANDING CHILDHOOD ADVERSITY AND PARENTAL ALCOHOLISM IN INDIA, A CROSS-SECTIONAL STUDY - Jayamohan, Anusree; Tomar, Shashi Prabha; Verma, Prashant (Journal of Public Health Research and Community Health Development, 2025)
Background: Traumatic incidents that happen before the age of eighteen, such as domestic abuse, violence, and child abuse, are known as adverse childhood experiences (ACEs). Unfortunately, the trend is on the increase globally. Long-term health problems like alcoholism, depression, and chronic illnesses can be brought on by these experiences. Girls are impacted differently by gender norms and conceptions, and adolescents affected by ACEs are more likely to experience health disparities.  Purpose: The current study is undertaken to estimate the prevalence and frequency of various types of ACEs among medical students in Jabalpur, Madhya Pradesh. Methods: A cross-sectional study, 211 NSCB Medical College students' data were gathered with the use of the "Adverse Childhood Experiences" (ACEs) scale. Chi square test was employed to determine the association. Results: As many as 211 medical students from NSCB Medical College in Jabalpur participated in the study; 19.4% of people were found to have an ACE with 10.5% of pupils saying they had only one ACE while 5.5% of pupils indicated that they had >/= 3 ACEs. Verbal abuse (6.2%) and family members who were problem drinkers or alcoholics (6.6%) were the most common ACEs reported. Conclusion: In spite of the low prevalence, a sizable portion stressed the significance of helping those who have experienced hardship. In order to lessen the negative effects of traumatic childhood experiences on mental health, the study emphasizes the necessity for additional investigation, education, and intervention. Determining the prevalence of adverse childhood experiences (in medical students is essential for developing focused interventions and support networks.